YL-0919, a dual 5-HT1A partial agonist and SSRI, produces antidepressant- and anxiolytic-like effects in rats subjected to chronic unpredictable stress - RAN Yu-hua; HU Xiao-xu; WANG Yu-lu; ZHAO Nan; ZHANG Li-ming; LIU Hua-xia; LI Yun-feng (Acta Pharmacologica Sinica, 2017)
Abstract YL-0919 has been identified as a novel dual 5-HT1A partial agonist and serotonin reuptake inhibitor. In the current study, we demonstrated that YL-0919 produced prominent antidepressant-like and anxiolytic-like effects in a chronic unpredictable stress (CUS) rat model. Male SD rats were exposed to CUS for 5 weeks; YL-0919 (1.25 and 2.5 mg/kg) or a positive control fluoxetine (Flx, 10 mg/kg) was orally administered daily. YL-0919 or Flx treatment significantly increased the sucrose preference rate, the locomotor activity in an open field test (OFT), the latency to feed in a novelty-suppressed feeding test (NSFT), and both the percentage of time spent in the open arms and the number of entries into the open arms in an elevated plus-maze test. YL-0919 or Flx treatment significantly suppressed the serum levels of ACTH and corticosterone in CUS-exposed rats. Additionally, YL-0919 or Flx treatment significantly enhanced the levels of cAMP, the expression of phosphorylated cAMP response element-binding protein (pCREB) and brain-derived neurotrophic factor (BDNF) in the hippocampus of CUS-exposed rats. Similar to Flx, YL-0919 treatment significantly enhanced the dendritic complexity, and increased the number of dendritic nodes as well as the spine length and number of branch nodes in the hippocampal pyramidal neurons of CUSexposed rats. Overall, our results reveal that YL-0919 suppresses the HPA axis and exerts antidepressant-like and anxiolytic-like effects in CUS-exposed rats, which are associated with the enhanced cAMP signaling and hippocampal dendritic complexity.